Myths-Based Local Wisdom of Rural Community - Abdul Hafidz; Muhammad Yusri AR; Rizky Marwani Bagus; Nur Aulia Rachman (Universitas Cokroaminoto Palopo, 2022)
Pamboborang Village is one of the villages in the District of Banggae, Majene Regency. Pamboborang Village which has a lot of potentials to be developed both in terms of tourism and natural resources. The location of this village is not far from the district city center so that this village can quickly obtain information, both the latest news and issues in the community. The people who live in this area have customs that are still practiced today. This attracted our attention to research further, because in the era of increasingly rapid development of technology and science, they still maintain their culture. The purpose of this study is to reveal the meaning of the myth that has been developing in the Pamboborang community, which is part of the community belonging to an educated society in the modern era. This study uses ethnographic qualitative research methods. The results of the research are expected to contribute to the world of education, especially to learn about matters related to humans and culture in general. The results of this study found that cultural activities carried out by the community which became a myth among the community contained the meaning of togetherness, respecting and carrying out the advice of their parents, and remembering the Creator in various situations. This should be maintained considering the increasingly rapid flow of science and technology development. So that later the myths that develop among them can be a medium to filter the impacts of the current science and technology development.